Peran Gaya Kepemimpinan Dalam Meningkatkan Kinerja Karyawan Dinas Kota Semarang - Ana Kadarningsih; Shalma Aprillia (Fakultas Ekonomi Universitas 45 Surabaya, 2019)
Employee performance is the result of the quantity and quality of the work process achieved by the employee in accordance with the duties and responsibilities of the employee. The higher the quality of employee performance, the higher the employee's work productivity. This study has a goal, namely to see how far the influence of work stress, leadership and compensation in improving employee performance. The population of this study were permanent employees who worked at the Department of Fisheries and Maritime Affairs of the City of Semarang, totaling 123 people. The research sample uses all population numbers. The research method uses multiple regression analysis with the addition of normality test, reliability test, validity test, hypothesis test and coefficient of determination test. The analysis tool uses SPSS version 21. The results show that leadership style has the greatest and most significant influence in improving employee performance. Work stress is the second largest order that affects employee performance negatively and significantly. While compensation is the third order in influencing employee performance positively and significantly.